Article with colored luminous pattern and preparation method thereof

By performing fluorosilane modification on the surface of the substrate, the contact angle of the oily droplets and the bonding of the ink are improved, the problem of difficult to take into account both printing accuracy and bonding in the prior art is solved, and the patterning effect of high precision and bonding is achieved.

CN119730571APending Publication Date: 2025-03-28CORE VISION (BEIJING) TECH CO LTD

Patent Information

Application Number
CN202411965936.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing inks containing quantum dot materials encounter difficulties in taking into account printing accuracy and bondability during the pattern refinement process, and their surface tension characteristics are different from conventional inks, so they cannot directly borrow their rules to improve printing precision and durability bonding.

Method used

By performing special modification treatment on the substrate surface, the substrate surface is hydrophobic with a silane compound containing fluorine atoms, so that the oily droplets have a suitable contact angle with the substrate surface, thereby improving the printing accuracy, and improving the bonding of the ink and the substrate through further silane coupling agent treatment.

Benefits of technology

It is possible to improve the printing accuracy in the patterning formation process, while maintaining or improving the bonding of the ink and the substrate surface, so as to form a pixel-level luminescent pattern.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730571A_ABST
    Figure CN119730571A_ABST
Patent Text Reader

Abstract

The invention provides a product with a luminous pattern and a preparation method thereof, the product comprises a base material and a luminous layer existing in at least partial area of the surface of the base material, the area, in contact with the luminous layer, of the base material is modified and then compounded with a material of the luminous layer, the base material comprises an inorganic non-metallic material, and the inorganic non-metallic material is a metal material. The light-emitting layer includes a quantum dot material having fluorescence characteristics, and the modification is to treat the region of the substrate using a silane compound containing fluorine atoms and an aliphatic group having 8 or more carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of materials, and to the field of nanomaterial applications and products. Specifically, it relates to a product based on quantum dots and a preparation method thereof. Background Art

[0002] Quantum dots (QDs) usually refer to nanocrystals with a radius smaller than or close to the Bohr radius of the exciton, especially semiconductor nanocrystals. The particle size of quantum dots is generally 1 nanometer to tens of nanometers, usually spherical or quasi-spherical. Since electrons and holes are quantum confined, the continuous energy band structure becomes a discrete energy level structure with molecular characteristics, and the band gap increases as the size decreases. Therefore, fluorescence can occur after being stimulated, and it has a variety of special physical effects (for example, quantum size effect, surface effect, dielectric confinement effect, quantum tunneling effect and Coulomb blockade effect, etc.).

[0003] At present, quantum dot materials are usually prepared from II-VI, IV-VI or III-V semiconductor materials. Common quantum dot materials include II-VI semiconductor quantum dots such as cadmium sulfide (CdS), cadmium selenide (CdSe), cadmium telluride (CdTe) and zinc sulfide (ZnS); IV-VI semiconductor quantum dots such as lead sulfide (PbS) and lead selenide (PbSe); III-V semiconductor quantum dots such as indium phosphide (InP) and indium arsenide (InAs). In addition, quantum dot materials based on perovskite structure and carbon quantum dot materials have also been developed. These materials have different hydrophilic or lipophilic properties according to the surface (ligand) properties. And under certain conditions, such as using ligand exchange, the conversion of the above two properties can be achieved.

[0004] Generally, quantum dot materials can be widely used in energy conversion, light-emitting display devices, photoelectric detection molecular probes, spectral equipment, biological markers and development.

[0005] Furthermore, methods for patterning using quantum dot materials have been widely studied, and for example, there have been many studies on printing or printing using ink containing quantum dot materials.

[0006] Reference 1 discloses a perovskite quantum dot dispersion for inkjet printing and photolithography patterning. The dispersion synthesizes perovskite quantum dots in a polymer monomer, a crosslinker and a photoinitiator by a one-pot method, and can achieve high dispersibility, high stability and high-resolution patterning of perovskite quantum dots in the process of inkjet printing and photolithography.

[0007] Reference 2 discloses a solvent-free photocurable quantum dot ink, which is prepared by mixing raw materials containing polythiol compounds, acrylic monomers or oligomers, and photoinitiators with a perovskite precursor liquid. It uses polymer monomers to dissolve the perovskite precursor, avoiding the use of traditional organic solvents.

[0008] Reference 3 This application discloses a quantum dot photoresist, quantum dot film and application thereof based on POSS. The quantum dot photoresist based on POSS comprises the following components: quantum dot raw material, POSS structural monomer, polythiol compound and organic solvent; the quantum dot raw material is perovskite quantum dot or perovskite quantum dot precursor. The quantum dot film based on POSS is obtained by coating and curing the quantum dot photoresist based on POSS. After cross-linking and curing, the POSS-based monomer forms a dense cross-linked network confined quantum dots, maintains a good uniform distribution of quantum dots, forms a stable dispersion system and improves the fluorescence intensity of quantum dots.

[0009] Furthermore, there is also a lot of common knowledge about patterning strategies using inks containing quantum dot materials, such as:

[0010] Reference 4 discloses a method for preparing high-density full-color QLED devices using full-inkjet printing, by formulating ink and optimizing performance for each functional layer material, and finally using inkjet printing technology to enable it to form a stable film on a specific substrate, in order to manufacture a full-inkjet printed electroluminescent QLED.

[0011] Reference 5 discloses a method for preparing a patterned quantum dot thin film light-emitting device, which comprises inkjet printing a metal interdigitated electrode of the light-emitting device on a glass substrate, and then inkjet printing a carrier injection layer, and depositing a patterned quantum dot thin film by ultrasonic spraying to obtain a patterned luminescent CsPbBr3 inorganic perovskite quantum dot light-emitting device.

[0012] It can be seen that the patterning methods and strategies for inks based on quantum dot materials have been studied, but there is still room for further improvement in terms of the convenience, diversification and quality of patterning.

[0013] References:

[0014] Reference 1: CN118530626A

[0015] Reference 2: CN118580717A

[0016] Reference 3: CN118567181A

[0017] Reference 4: CN117835769A

[0018] Reference 5: CN116963566A Summary of the invention

[0019] Problem that the invention aims to solve

[0020] As mentioned above, the current research on forming patterns containing quantum dot materials by printing and other methods mainly focuses on the research of quantum dot materials themselves or inks containing them. In addition, for patterning strategies, the focus is usually only on the control method of the process.

[0021] For the current technology, in terms of the quality of patterning (such as resolution, bonding, durability, etc.), it is more based on the ink containing quantum dots itself, because usually, the bonding of the light-emitting layer and the substrate layer that form the pattern can be achieved with the help of the curable organic components in the ink.

[0022] However, it is found in continuous practice that the existing oily ink containing quantum dot materials has also encountered increasing limitations in the process of pattern refinement. On the one hand, it is observed that although the hydrophobic surface and the oily ink droplet have good binding properties in theory, it is precisely because of this good binding property that the contact angle between the two becomes smaller, and in this case, the printing accuracy is often suppressed; on the other hand, although it is believed that in the above case, the appropriate increase in the contact angle is conducive to improving the fineness of printing, it is also found that such adjustment may lead to the deterioration of the binding properties of the printed pattern and the substrate, especially the deterioration of the binding properties of the quantum dot materials contained in the ink, which is easy to cause peeling over time. Therefore, the above factors are difficult to take into account (trade-off) problems. In addition, since the ink containing quantum dot materials is different from conventional inks in terms of surface tension, the precision and durable binding properties of printing cannot be obtained from the rules of conventional inks in the past.

[0023] In addition, regarding the problem of the binding of quantum dot materials with inorganic substrates, some existing technologies have proposed quantum dot surface modification solutions for silica microspheres, which use chemical bonding to impart quantum dot materials to the silica surface. However, this method is not applicable when dealing with patterning processes such as printing and photolithography.

[0024] Through long-term research, in order to solve the above technical problems, the present invention proposes that, in view of the particularity of ink containing quantum dot materials, a special modification treatment is performed on the surface of the substrate, so that when the ink containing quantum dot materials is printed, the contact angle between the oil droplet and the substrate surface is suitable, and the contact angle improves the printing accuracy, and can also satisfy the ink or quantum dot material and the substrate surface to achieve good combination. That is, the process of the present invention not only improves the printing accuracy in the patterning process by surface treatment of the substrate characteristics, but also maintains or improves its combination with the quantum dot material, and can further provide a pixel-level luminous pattern.

[0025] Solutions for solving problems

[0026] It has been found that the above technical problems can be solved by implementing the following technical solutions:

[0027] [1] The present invention first provides a product having a luminous pattern, wherein the product comprises:

[0028] A substrate, and a light-emitting layer present on at least a portion of the surface of the substrate,

[0029] The substrate is modified in the region in contact with the light-emitting layer and then composited with the material of the light-emitting layer.

[0030] in,

[0031] The substrate comprises an inorganic non-metallic material, the light-emitting layer comprises a quantum dot material having fluorescent properties,

[0032] The modification includes treating the region of the substrate with a silane compound (A), and the silane compound (A) contains a fluorine atom and an aliphatic group having 8 or more carbon atoms.

[0033] [2] The article according to [1], wherein the substrate is formed of a silicon-containing material; and the substrate includes a planar region, a curved region, or any combination thereof.

[0034] [3] The article according to [1] or [2], wherein the light-emitting layer is present on the surface of the region of the substrate or is at least partially embedded in the region.

[0035] [4] The article according to any one of [1] to [3], wherein the light-emitting layer comprises one or more quantum dot materials; the quantum dot materials have ligands, and the ligands have or do not have polymerizable groups.

[0036] [5] The product according to any one of [1] to [4], wherein the aliphatic group contained in the silane compound (A) has 10 to 18 carbon atoms; and the fluorine atom is present on the aliphatic group.

[0037] [6] The article according to any one of [1] to [5], wherein the modification further comprises surface treatment of at least part of the surface of the area treated with the silane compound using an additional silane compound (B) containing an acrylate group, wherein the silane compound (B) has an unsaturated group or a group that can form a hydrogen bond with a ligand of the quantum dot material of the light-emitting layer.

[0038] [7] The product according to any one of [1] to [6], wherein the product further comprises a filter film, wherein the filter film has a cutoff capability of at least light below 400 nm.

[0039] [8]. Furthermore, the present invention also provides a method for preparing the product according to any one of [1] to [7], wherein the method comprises:

[0040] A step of modifying the surface of the substrate, using the silane compound (A) to treat the area on the surface of the substrate;

[0041] a step of forming a light-emitting layer to impart the quantum dot material to the surface-treated area of ​​the substrate;

[0042] Optionally, before the step of modifying the surface of the substrate, the method further includes a step of activating the surface of the substrate.

[0043] [9] The method according to [8], wherein the imparting comprises any one of inkjet printing, photolithography, evaporation, and silk screen printing.

[0044]

[10] The method according to [9], wherein the method further comprises a packaging step to encapsulate at least the light-emitting layer.

[0045] Effects of the Invention

[0046] By implementing the above technical solution, the present invention can achieve the following technical effects:

[0047] 1) By treating the surface of the inorganic non-metallic material substrate, especially using a silane coupling agent containing fluorine atoms, the substrate surface is given suitable hydrophobicity. When printing with ink containing quantum dot materials, the oil droplets have a suitable contact angle on the substrate surface, which is beneficial to improve the resolution of the formed image, thereby being able to form a pixel-level luminous pattern.

[0048] 2) The above-mentioned fluorine-containing silane coupling agent treatment can also maintain or improve the bonding strength between the ink and the substrate surface, especially maintain or improve the bonding between the quantum dot material in the ink and the substrate surface.

[0049] 3) In some preferred embodiments of the present invention, by treating with other silane coupling agents (silane compounds (B) containing acrylate groups), the bonding between the substrate and the quantum dot material can be further increased, thereby improving the weather resistance and durability of the final pattern. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 : Schematic diagram of the contact angle between ink and substrate surface in Experimental Examples 1-3

[0051] Figure 2 : Schematic diagram of the contact angle between ink and substrate surface in Experimental Examples 4-8

[0052] Figure 3 : In Example 1, the adhesion of the patterns under the two treatment methods was tested using a grid knife (the left is Example 1a, and the right is Example 1b)

[0053] Figure 4 : Fluorescence image of the pattern obtained in Example 2

[0054] Figure 5 : Fluorescence image of the pattern obtained in Example 3

[0055] Figure 6 : Luminous spectrum of the pattern obtained in Example 4 after being filtered by the filter film DETAILED DESCRIPTION

[0056] The following is a detailed description of the present invention. The technical features described below are described based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples.

[0057] It should be noted that:

[0058] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0059] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model or theoretical data is within a range of 1%, preferably 0.9%, and more preferably 0.8%.

[0060] In this specification, unless otherwise specified, "%" means mass percentage.

[0061] In this specification, "room temperature" is used to refer to a temperature range of 23±2°C.

[0062] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0063] In this specification, the term "plurality" or "multiple" refers to a number greater than 2.

[0064] In this specification, the ultraviolet absorption peak / the wavelength corresponding to the peak described in the present invention refers to the (first) absorption peak that can be tested within the test range or the wavelength corresponding to the peak (scanning the wavelength from low to high), and such absorption peak is the main absorption peak considered in the art (e.g., the peak with the largest or larger peak area).

[0065] In this specification, unless otherwise specified, "quantum dot" and "quantum dot material" have equivalent physical and chemical meanings.

[0066] In this specification, unless otherwise specified, "unsaturated" means "polymerizable". In this specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes the case where the event occurs and the case where the event does not occur.

[0067] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0068] The present invention mainly provides a product with a luminous pattern and a preparation method thereof. The present invention is mainly obtained through the following insights:

[0069] When printing with ink containing quantum dot materials, although the surface of the substrate is hydrophobically treated to improve the affinity between the ink and the substrate surface, this method also has obvious defects in today's increasingly high demand for high-precision printing. Therefore, the present invention explores from the perspective of contact angle, and through a specific surface treatment method, the ink droplet is given a suitable contact angle with the substrate surface, thereby balancing the printing accuracy and ink binding.

[0070] [First aspect]

[0071] The first aspect of the present invention provides a product having a luminescent pattern, wherein the product comprises: a substrate, and a luminescent layer present on at least a portion of the surface of the substrate.

[0072] The substrate is modified in the area in contact with the light-emitting layer and then composited with the material of the light-emitting layer, wherein the substrate includes an inorganic non-metallic material, the material of the light-emitting layer includes a quantum dot material with fluorescent properties, the modification includes treating the area of ​​the substrate with a silane compound (A), and the silane compound (A) contains fluorine atoms and aliphatic groups with more than 8 carbon atoms.

[0073] (Base material)

[0074] The substrate of the present invention may include various inorganic non-metallic materials. Preferably, the substrate of the present invention allows ultraviolet excitation light to pass through and may be colorless or have various colors.

[0075] Such inorganic non-metallic materials may be carbon-based, nitrogen-based, silicon-based inorganic materials, or inorganic materials formed by any two elements of carbon, nitrogen, and silicon. In addition, inorganic non-metallic materials may also be oxides formed by various metals.

[0076] The inorganic non-metallic material mentioned above may be formed from one material or may be formed by compounding multiple materials, wherein the compounding may include a physical process or a chemical process.

[0077] In some specific embodiments, the substrate described in the present invention is substantially formed by the inorganic non-metallic material.

[0078] In some preferred embodiments of the present invention, the inorganic non-metallic material of the present invention can be selected from various silicon-containing inorganic materials, such as silicon oxides, inorganic substances formed by silicon and carbon or silicon and nitrogen. More preferably, the inorganic non-metallic material of the present invention can be silicate or silicon dioxide, for example, glass.

[0079] The shape of the substrate of the present invention is not particularly limited in principle, and it can be plate-shaped, sheet-shaped, columnar or any shape, and these shapes can have a flat surface area, any curved surface area or a combination thereof. The size of the substrate of the present invention is not particularly limited, and can have a geometric size of centimeters or more.

[0080] In some preferred embodiments of the present invention, the substrate of the present invention may be a (transparent) glass plate, such as quartz glass, high borosilicate glass, and the like.

[0081] In addition, in some specific embodiments, a portion of the substrate surface area is used to form the light-emitting layer to be described below, or the entire substrate (main) surface area is used to form the light-emitting layer.

[0082] (Silane compound (A))

[0083] The silane compound (A) of the present invention is used to perform surface treatment on a predetermined surface area of ​​the substrate of the present invention. The silane compound can not only improve its hydrophobicity, ensure the binding property of the quantum dot material in the ink with the surface of the substrate, but also better control the contact angle when the ink droplet contacts the substrate, thereby facilitating the improvement of printing accuracy.

[0084] The silane compound (A) of the present invention has a fluorine atom, an aliphatic group having 10 or more carbon atoms, and a hydrolyzable group in its molecular structure.

[0085] Such medium- and long-chain aliphatic groups can, on the one hand, obtain suitable hydrophobicity, and on the other hand, can increase compatibility with the ligands of the quantum dot materials in the light-emitting layer to be described below, thereby being able to form a bond with these quantum dot materials.

[0086] In some preferred embodiments of the present invention, the aliphatic group may be an aliphatic group having 10 to 18 carbon atoms, especially a straight-chain aliphatic group, specifically a (straight-chain) aliphatic group having 12, 14, or 16 carbon atoms.

[0087] Furthermore, the above-mentioned aliphatic group may be a saturated aliphatic group or an unsaturated aliphatic group. Preferably, in the unsaturated aliphatic group, the degree of unsaturation does not exceed 2, and is preferably 1, from the perspective of stability.

[0088] Further, the existence form of the fluorine atoms in the silane compound (A) of the present invention is not particularly limited in principle, and the fluorine atoms may be on the above-mentioned aliphatic groups, and one or all of the hydrogen atoms in these aliphatic groups may be replaced by fluorine atoms. In addition, the fluorine atoms may also exist on other groups of the silane compound.

[0089] In some preferred embodiments, the number of fluorine atoms in the silane compound (A) of the present invention is greater than or equal to the number of carbon atoms therein, and more preferably, the number of fluorine atoms in the silane compound of the present invention is greater than or equal to the number of carbon atoms in the aliphatic group therein. Such control can better obtain the desired hydrophobicity and the degree of tightness of binding with quantum dots.

[0090] Furthermore, the hydrolyzable group in the silane compound (A) is generally used to fix the silane compound (A) to the surface of the substrate. In principle, there is no particular limitation on such a hydrolyzable group, and it may be, for example, a methoxy group, an amino group, a halogen group, or the like.

[0091] In some specific embodiments of the present invention, the silane compound (A) can be typically selected from one or more of methoxyfluoroalkylsilane, aminofluoroalkylsilane, perfluorodecyltrichlorosilane and the like.

[0092] (Silane compound (B))

[0093] In some preferred embodiments of the present invention, after the surface of the substrate is treated with the above-mentioned silane compound (A), a part or the entire area of ​​the treated area may be further treated with a silane compound (B).

[0094] By further using the silane compound (B), the binding property between the substrate surface and the quantum dot material in the ink can be further improved.

[0095] Specifically, the silane compound (B) of the present invention has an unsaturated group or a group capable of forming a hydrogen bond with a quantum material ligand in the ink in addition to a hydrolyzable group.

[0096] The above-mentioned unsaturated groups may generally be (meth)acrylate unsaturated groups; the above-mentioned groups capable of forming hydrogen bonds may generally be groups containing active hydrogen, such as amino groups or imino groups.

[0097] Such a silane compound (B) may not significantly affect the contact angle of the ink droplet, and can also improve the binding property between the substrate and the quantum dot material by improving the binding property with the quantum dots (ligands).

[0098] In some preferred embodiments of the present invention, the silane compound (B) may include: 3-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and the like.

[0099] (Luminous layer)

[0100] The light-emitting layer of the present invention is mainly used to cover at least a portion of the surface of the above-mentioned substrate to provide the required optical properties.

[0101] In some specific embodiments, the light-emitting layer covers more than 20 area % of the surface of the substrate (main surface), preferably more than 30 area %, more than 40 area %, more than 50 area %, more than 60 area %, more than 70 area %, more than 80 area %, more than 90 area % or even substantially all of the surface.

[0102] Furthermore, the light-emitting layer of the present invention includes quantum dot materials and other optional components.

[0103] In principle, there is no special restriction on the quantum dot materials used to form the light-emitting layer as long as they have fluorescent properties. They can be various lipophilic or hydrophilic quantum dot materials, with lipophilic quantum dot materials being particularly preferred. Specifically, for example, they can include semiconductor quantum dot materials or be essentially composed of them.

[0104] In some specific embodiments, the semiconductor quantum dot material can be selected from one or more of Group II-VI semiconductor quantum dot materials, Group IV-VI semiconductor quantum dot materials, Group III-V semiconductor quantum dot materials, or composites thereof.

[0105] In some specific embodiments of the present invention, the quantum dot material may include II-VI semiconductor quantum dot materials such as cadmium sulfide (CdS), cadmium selenide (CdSe), cadmium telluride (CdTe) and zinc sulfide (Zns); IV-VI semiconductor quantum dot materials such as lead sulfide (PbS) and lead selenide (PbSe); III-V semiconductor quantum dot materials such as indium phosphide (InP) and indium arsenide (InAs); and quantum dot materials with a core-shell structure such as CdS / ZnS, CdSe / CdS, CdSe / ZnS, CdSe / CdS / ZnS, CdTe / CdS, CdTe / CdS / ZnS, ZnSe / ZnS, InP / ZnSe, InP / ZnS, InP / ZnSe / ZnS, InP / GaP / ZnS, etc.

[0106] There is no particular limitation on the method for forming the quantum dot material. The quantum dot material may be synthesized by hot injection of an organic medium-based quantum dot material. First, the raw materials are dissolved in an organic solvent or a ligand to form a precursor, and then mixed under heating conditions to form the quantum dot material through a chemical reaction.

[0107] In some specific embodiments of the present invention, the above ligands may be compounds with polar ends and a certain chain length, and preferably, these compounds also have polymerizable unsaturated groups.

[0108] In some specific embodiments of the present invention, the ligand may be an aliphatic compound, and the aliphatic compound may be a compound having an aliphatic group with 14 to 25 carbon atoms, especially a compound having a straight-chain aliphatic group. Specific examples include (straight-chain) aliphatic groups with 16, 18, 20, and 22 carbon atoms.

[0109] Furthermore, the above-mentioned aliphatic group may be a saturated aliphatic group, and preferably, may be an unsaturated aliphatic group. In the unsaturated aliphatic group, the degree of unsaturation does not exceed 2, and is preferably 1, from the perspective of stability.

[0110] In some other embodiments of the present invention, the ligand may also be an alicyclic or aromatic compound. There is no particular limitation on these specific structures in principle. For these ligands, the unsaturation degree is preferably not more than 2, and more preferably 1.

[0111] The polar terminal mentioned above can generally be one or more of an amine group, a thiol group, a carboxyl group or an ether group. Preferably, the aliphatic compound has one polar terminal.

[0112] Furthermore, the solvent used in the synthesis of the quantum dot material may preferably be various non-polar solvents or weakly polar solvents, such as octadecene, diphenyl ether, paraffin oil, and the like.

[0113] In addition, there is no particular limitation on the particle size of the quantum dot material. In some specific embodiments of the present invention, the particle size of the quantum dot material may be 1 to 100 nm. Preferably, the particle size range may be 2 to 70 nm, more preferably 3 to 50 nm, and further preferably 4 to 30 nm or 5 to 20 nm.

[0114] In principle, there is no particular limitation on other optional components that can be used in the light-emitting layer of the present invention. These components can be derived from the ink composition used in the process of preparing the light-emitting layer.

[0115] In some specific embodiments, these optional components may include organic resins, auxiliary agents, etc. The organic resin may assist in bonding the light-emitting layer to the surface of the substrate by curing.

[0116] In the light-emitting layer of the present invention, the content of the quantum dot material is 80% by mass or more, preferably 85% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, based on the total mass of the light-emitting layer.

[0117] In principle, the thickness of the light-emitting layer of the present invention is not particularly limited and can be adjusted according to different formation methods.

[0118] Furthermore, the light-emitting layer of the present invention can have any pattern, and these patterns can have the same optical properties, such as emitting light of the same wavelength (i.e., forming a pattern of one color), or emitting light of different wavelengths through different types of quantum dot materials, thereby forming a pattern of multiple colors, preferably more than 3 colors, and more preferably 3 to 10 colors.

[0119] In addition, the light-emitting layer of the present invention may be formed on the surface of the substrate in some specific embodiments, and may be at least partially embedded under the surface of the substrate in other specific embodiments.

[0120] (Other parts)

[0121] The product of the present invention may include other components as required in addition to the substrate and the light-emitting layer described above.

[0122] In some specific embodiments, these components may be packaging components, filtering components, and the like.

[0123] The packaging component is mainly used to package the above-mentioned light-emitting layer to provide necessary protection, thereby improving the durability of the light-emitting layer. Such a packaging component can be a transparent film layer, which can isolate oxygen and moisture and provide transmittance to ultraviolet light. In principle, there is no special restriction on the formation method of the packaging component, and the usual process can be evaporation, spin coating, spraying, infusion, etc.

[0124] The filter component mainly plays a protective role for viewers and can be used to cut off ultraviolet light that is harmful to the human body. The source of these ultraviolet lights can be the ultraviolet light used to excite the quantum dot material of the light-emitting layer of the present invention.

[0125] In some specific embodiments, these filter components include a filter film, which has at least a cutoff capability for light below 400nm, for example, a cutoff capability for light below 450nm. In some specific embodiments, the filter film can be a long-pass filter film capable of cutting off ultraviolet light with a wavelength below 380nm, and typical examples include: a CdS material long-pass filter film capable of filtering light sources below 365nm, a ZnS material long-pass filter capable of filtering ultraviolet light below 300nm, etc.

[0126] (Products)

[0127] In principle, there is no particular limitation on the type of the product having a luminous pattern of the present invention, and examples thereof include display components, decorative components, lighting components, and the like.

[0128] [Second aspect]

[0129] In a second aspect of the present invention, a method for preparing the product having a luminous pattern in the first aspect is provided.

[0130] Specifically, the method comprises:

[0131] A step of modifying the surface of the substrate, using the silane compound (A) to treat the area on the surface of the substrate;

[0132] The step of forming a light-emitting layer is to impart the quantum dot material to the surface-treated area of ​​the substrate.

[0133] Furthermore, optionally, before the step of modifying the surface of the substrate, the method further includes a step of activating the surface of the substrate.

[0134] (Activation treatment steps)

[0135] Before using the silane compound (A) of the present invention to modify the substrate surface, the substrate surface may be activated in advance by various activation means to increase the binding property between the silane compound (A) and the substrate surface.

[0136] The activation treatment can be achieved by imparting suitable hydrophilic groups to the substrate surface, such as hydroxyl, amine, carboxyl, sulfonic acid, thiol or groups that can generate these groups by hydrolysis.

[0137] In principle, there is no particular limitation on such activation treatment, and it can be carried out, for example, by etching, acid solution treatment, etc. Optionally, heating treatment can be carried out during the treatment as required. The methods that can be listed include wet and dry methods, wherein the wet method includes solvent cleaning, piranha lotion cleaning, etc.; the dry method includes plasma cleaning, UV-O3 cleaning, etc.

[0138] (Step of modifying the surface of the substrate)

[0139] Further, the activated substrate is treated with the silane compound (A). The silane compound (A) can be dissolved with a hydrocarbon solvent, and then the predetermined surface area of ​​the substrate is treated with its steam or directly immersed or coated. After the treatment, it can be dried for standby use. There is no particular restriction on the treatment time in principle. In some specific embodiments, it can be adjusted according to the required contact angle (ink). In other specific embodiments, the substrate surface can be fully treated by treating for 2 to 6 hours or 3 to 5 hours.

[0140] Furthermore, if necessary, the above treatment may be followed by further treatment using the above-mentioned silane compound (B).

[0141] The area after the above surface modification treatment exhibits hydrophobicity.

[0142] In some specific embodiments of the present invention, the contact angle between the substrate surface and the oily ink obtained by the above-mentioned modification treatment can be controlled to be 60-100°, preferably, it can be controlled to be 65-95°, more preferably 70-90°, and further preferably 70-85°. It should be noted that the present invention allows the contact angle between the oily ink and the substrate to be greater than 90°, mainly because such an angle is conducive to improving the printing accuracy, and at the same time, it can also maintain the binding property between the substrate and the quantum dot material in the oily ink.

[0143] (Formation of Light Emitting Layer)

[0144] The formation of the light-emitting layer of the present invention can be achieved by using a (ink) composition containing the above-mentioned quantum dot material.

[0145] Composition

[0146] Such a composition may be a dispersed system containing quantum dot materials.

[0147] Further, there is no particular limitation on the specific composition of the composition, which is related to the form of the light-emitting layer formed by the composition. In some specific embodiments, the composition may contain quantum dot materials, reactive diluents, initiators and other auxiliary agents, and optionally, other resin components.

[0148] The concentration range of the quantum dot material can be controlled within a range of no more than 100 mg / mL. Examples include 0.1-90 mg / mL, 0.5-85 mg / mL, 1-80 mg / mL, 5-75 mg / mL, 10-70 mg / mL, 15-65 mg / mL, 20-60 mg / mL, 25-55 mg / mL, 30-50 mg / mL, etc. The concentration of the quantum dot material can determine the light intensity or brightness of the final pattern.

[0149] In principle, there is no particular limitation on the viscosity of the composition of the present invention, as long as it can meet the needs of subsequent processes. In some preferred embodiments of the present invention, such viscosity can be 500 cps or less at room temperature, such as 1-450 cps, 5-400 cps, 10-350 cps, 15-300 cps, 20-250 cps, etc.

[0150] Patterning

[0151] Regarding the method for forming the pattern of the light-emitting layer of the present invention, the processes that can be generally listed include inkjet printing (including ordinary inkjet printing and electrohydrodynamic inkjet printing (Electrohydrodynamic Inkjet Printing, referred to as EHD or E-jet Printing)), photolithography, evaporation, silk screen printing, etc. From the perspective of the convenience of precision control, it is preferably carried out by inkjet printing and photolithography.

[0152] For inkjet printing, the raw material system can be an ink system, which includes quantum dot materials, diluent monomers, (photo) initiators and additives. The quantum dot concentration range is 0.1-100 mg / ml, the quantum yield is ≥70%, and the quantum dot fluorescence wavelength is within the visible range. In addition, the requirements for the ink system are: good dispersibility, viscosity range of 1-300 cps, preferably, the tension range can be 10-70 mN / m, etc.

[0153] For the photolithography process, the raw material system is a photoresist system, and its components may include quantum dot materials, resins, diluent monomers, (photo) initiators and additives, etc. Among them, the concentration range of the quantum dot material is 0.1-100 mg / ml, the quantum yield is ≥70%, and the quantum dot material can be selected with a fluorescence wavelength within the visible range. The requirements for the photoresist system are: good dispersibility, viscosity range of 1-300 cps, spin coating film forming performance, good substrate adhesion, etc.

[0154] In addition, for other designs of patterning, there is no special pattern. For example, the desired pattern can be formed once with the help of the patterning method, or the desired pattern can be formed multiple times using compositions with different luminescent properties.

[0155] The methods of forming the pattern of various colors on the substrate may be:

[0156] i. The pattern to be printed is split into multiple pictures by color.

[0157] ii. Each image is printed separately on the substrate, and each color is overprinted together to form the target pattern. For multiple overprints, there may be pixel accuracy control, which can be achieved by setting the alignment point, and multiple colors can be calibrated with this point as the reference point.

[0158] The process can be controlled by using existing computer programs.

[0159] In some specific implementations, the final print volume is selected based on the different print volumes of each material, the brightness of the fluorescent material, and the visual effect, wherein the print volume can be adjusted within a certain range (the adjustable space of each ratio is 0-100 times) and matched. The print volume is one of the device parameters and can be entered into the device and set separately. The input device information includes a series of parameters such as the coordinate position of the print, the print volume, etc.

[0160] (Other steps)

[0161] The other steps of the method for manufacturing the product of the present invention are not particularly limited in principle, and may include a packaging step and a step of installing other components.

[0162] For the encapsulation step, a transparent protective film layer may be provided to encapsulate and protect the light-emitting pattern formed above.

[0163] In some specific embodiments, the encapsulation can be in the form of thin film encapsulation and integral encapsulation:

[0164] i. The thin film packaging method is to integrate a layer of water-proof and oxygen-proof, ultraviolet-transmissive thin film on the pattern. The process can be evaporation, spin coating, spraying, infusion, etc.;

[0165] ii. The overall packaging method is to attach another layer of substrate above the pattern layer and package it on the outside. The packaging method can be casting, bonding, sealing pads, etc.

[0166] For the step of installing other components, for example, the step of including the filter component described above may be provided.

[0167] Example

[0168] The embodiments of the present invention are described in detail below with reference to the examples. If no specific conditions are specified in the examples, the reaction is carried out according to conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0169] Experimental Examples 1 to 3

[0170] Experimental Example 1:

[0171] The quartz substrate was cleaned, and then the surface of the substrate was modified with octadecyltrichlorosilane (OTS) (treated for about 2 hours), and the contact angle with the quantum dot ink was tested. The preparation and composition of the ink are as follows: 50 mg / mL of CdSe fluorescent quantum dots with oleic acid ligands are dispersed in a solvent system of a mixed solvent of toluene and o-dichlorobenzene with a volume ratio of 4:1 to obtain an oil-soluble quantum dot ink.

[0172] Experimental Example 2:

[0173] The same as Experimental Example 1, except that OTS was replaced with phenyltrichlorosilane (PTS), and the contact angle test was performed according to the same protocol.

[0174] Experimental Example 3:

[0175] The contact angle test was performed in the same manner as in Experimental Example 1, except that OTS was replaced with 1H,1H,2H,2H-perfluorodecyltrichlorosilane (FDTS).

[0176] The contact angles of each test in the experimental example are shown in Table 1 below:

[0177] Table 1:

[0178] Experimental Example 1 Experimental Example 2 Experimental Example 3 Coupling agent type OTS PTS FDTS Contact angle (degrees) 41.1 54.5 71.3

[0179] See Figure 1 As shown in the above experimental examples, it can be seen that the surface treatment of various silanes can change the hydrophobic properties of the treated surface, and too low a contact angle with the quantum dot ink will cause a decrease in printing accuracy.

[0180] Experimental Examples 4 to 8

[0181] Experimental Example 4:

[0182] The same quartz substrate and ink as those in Experimental Example 1 were used. In addition, the substrate was treated with FDTS for 0 hours and then treated with 3-methacryloxypropyltrimethoxysilane. The contact angle was then measured.

[0183] Embodiment 5~8:

[0184] Same as Example 4, except that the FDTS treatment time was 0.5 hour, 2 hours, 4 hours and 6 hours, respectively.

[0185] The contact angles of Experimental Examples 4 to 8 are shown in Figure 2 It can be seen that even if 3-methacryloxypropyltrimethoxysilane is additionally used, the contact angle can be controlled within a relatively ideal range.

[0186] Example 1

[0187] (Choice of base material)

[0188] The substrate is made of quartz glass that can transmit excitation light with an excitation wavelength of 365 nm.

[0189] (Processing of base materials)

[0190] 1. Plasma cleaning of quartz glass;

[0191] 2. Treat the cleaned quartz glass using the following method:

[0192] 2.1 Mix perfluorodecyl trichlorosilane coupling agent with n-octane solvent;

[0193] 2.2 Soak the quartz glass treated in step 1 in the solution prepared in step 2.1 (about 2 hours);

[0194] 2.3 After taking it out, clean it with alcohol and blow it dry with nitrogen.

[0195] 3. Dissolve 3-methacryloxypropyltrimethoxysilane in a mixture of ethanol and water, and spray the resulting solution on the quartz glass obtained in step 2 and dry it. The volume ratio of 3-methacryloxypropyltrimethoxysilane to the mixture of ethanol and water is 2:8, and the volume ratio of ethanol to water is 9:1.

[0196] (Forming a pattern)

[0197] Preparation of ink: 45% by weight of dodecyl acrylate, 2% by weight of hydroxycyclohexane phenone, and 53% by weight of CdSe fluorescent quantum dots containing (E)-3-(3-hydroxyphenyl) acrylic acid ligands with a wavelength of 630 nm are mixed to obtain quantum dot ink.

[0198] Ink coating formation: The ink was inkjet printed on the quartz substrate treated in steps 1 to 2 or in steps 1 to 3, and cured with a UV lamp to form a pattern. The two were then immersed in water for a week and dried. The patterns on both were intact with no obvious difference.

[0199] (Adhesion Test)

[0200] The above two films prepared by the two treatment methods were tested for adhesion using a grid knife. The test showed that the adhesion of the pattern treated by steps 1 to 3 (Example 1a) and the pattern treated only by steps 1 to 2 (Example 1b) were evaluated as follows:

[0201] The pattern of Example 1a after steps 1 to 3 ( Figure 3 Left) Even after severe damage, the non-edge part basically maintains good adhesion;

[0202] The pattern of Example 1b in which only steps 1 to 2 are performed ( Figure 3 (Right) Although damage occurred during the severe destruction, the non-edge part did not completely peel off as a whole, so it still shows good adhesion.

[0203] Example 2

[0204] (Choice of base material)

[0205] The substrate is made of quartz glass that can transmit excitation light with an excitation wavelength of 365 nm.

[0206] (Processing of base materials)

[0207] 1. Plasma cleaning of quartz glass;

[0208] 2. Treat the cleaned quartz glass using the following method:

[0209] 2.1 Mix perfluorodecyl trichlorosilane coupling agent with n-octane solvent;

[0210] 2.2 Soak the quartz glass treated in step 1 in the solution prepared in step 2.1 (about 2 hours);

[0211] 2.3 After taking it out, clean it with alcohol and blow it dry with nitrogen.

[0212] (Formation of Luminous Pattern)

[0213] Preparation of ink: 45% by mass of dodecyl acrylate, 2% of hydroxycyclohexane phenone, and 53% by mass of CdSe quantum dots containing (E)-3-(3-hydroxyphenyl) acrylic acid ligands with wavelengths of 470nm, 540nm, 580nm and 630nm are mixed to obtain fluorescent quantum dot inks capable of emitting four colors of light: red, green, orange and blue, and the inks are loaded into four ink cartridges of an inkjet printer respectively.

[0214] The above multi-color ink is formed on the quartz glass obtained in the above (treatment of the base material) step 2.3:

[0215] 1) Split the image to be printed into multiple images by color.

[0216] 2) Each image obtained in step 1) is printed on quartz glass in sequence by inkjet printing, and each color is overprinted together to form a target pattern to obtain a light-emitting layer.

[0217] 3) The printed multi-color target pattern is cured by ultraviolet light.

[0218] (Protect the printed luminous layer)

[0219] A water- and oxygen-blocking, ultraviolet-transparent thin film is spin-coated on the light-emitting layer.

[0220] The luminescence pattern under 365 nm UV light is shown in Figure 4 .

[0221] Figure 4 There are four colors in total: red, green, orange and blue. The particle size of each dot pattern in each color is about 10 microns.

[0222] Example 3

[0223] Step 3 is added after step 2 in (treatment of substrate material) of Example 2, and the ink preparation step in (formation of luminous pattern) is replaced as follows, and the replaced ink is formed on the quartz glass obtained in step 3, and after printing the pattern, UV curing is not performed. Other than this, the other conditions are the same as those in Example 2.

[0224] Step 3:

[0225] Dissolve γ-methacryloxypropyltrimethoxysilane in a mixture of ethanol and water, spray the solution obtained on the quartz glass obtained in step 2 and dry it, wherein the volume ratio of γ-methacryloxypropyltrimethoxysilane to the mixture of ethanol and water is 2:8, and the volume ratio of ethanol to water is 9:1.

[0226] Ink preparation:

[0227] Fluorescent CdSe quantum dots with oleic acid ligands with wavelengths of 470nm, 540nm and 630nm were dispersed in a solvent system consisting of a mixed solvent of toluene and o-dichlorobenzene in a volume ratio of 4:1 to prepare three kinds of fluorescent quantum dot inks with a mass concentration of 50mg / mL, and were loaded into three ink cartridges of an inkjet printer respectively.

[0228] The resulting multi-color fluorescent pattern, see Figure 5 .

[0229] Figure 5 There are three colors in total: red, green and blue. The particle size of each dot pattern in each color is about 10 microns.

[0230] Example 4

[0231] The following steps were added after the final step of Example 2. Other conditions were the same as those of Example 10.

[0232] A CdS long-pass filter film is spin-coated on the protective layer film. Its excitation luminescence spectrum is shown in Figure 6 .

[0233] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0234] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A product having a luminous pattern, characterized in that: The product comprises: A substrate, and a light-emitting layer present on at least a portion of the surface of the substrate, The substrate is modified in the region in contact with the light-emitting layer and then composited with the material of the light-emitting layer. in, The substrate comprises an inorganic non-metallic material, the light-emitting layer comprises a quantum dot material having fluorescent properties, The modification includes treating the region of the substrate with a silane compound (A), and the silane compound (A) contains a fluorine atom and an aliphatic group having 8 or more carbon atoms.

2. The product according to claim 1, characterized in that The substrate is formed of a silicon-containing material; the substrate includes a planar region, a curved region or any combination thereof.

3. The product according to claim 1 or 2, characterized in that: The light-emitting layer is present on the surface of the substrate in the region or is at least partially embedded in the region.

4. The product according to any one of claims 1 to 3, characterized in that The light-emitting layer includes one or more quantum dot materials; the quantum dot materials have ligands, and the ligands have or do not have polymerizable groups.

5. The product according to any one of claims 1 to 4, characterized in that The carbon number of the aliphatic group contained in the silane compound (A) is 10 to 18; and the fluorine atom is present on the aliphatic group.

6. The product according to any one of claims 1 to 5, characterized in that The modification further includes additionally treating at least a portion of the surface of the region treated with the silane compound with a silane compound (B), wherein the silane compound (B) has an unsaturated group or a group capable of forming a hydrogen bond with a ligand of the quantum dot material of the light-emitting layer.

7. The product according to any one of claims 1 to 6, characterized in that The product also has a filter film, which has a cutoff capability of at least light below 400 nm.

8. The method for preparing the product according to any one of claims 1 to 7, characterized in that: The method comprises: A step of modifying the surface of the substrate, using the silane compound (A) to treat the area on the surface of the substrate; A step of forming a light-emitting layer to impart the quantum dot material to the surface-treated area of ​​the substrate; Optionally, before the step of modifying the surface of the substrate, the method further includes a step of activating the surface of the substrate.

9. The method according to claim 8, characterized in that The imparting includes any one of inkjet printing, photolithography, evaporation, and silk screen printing.

10. The method according to claim 9, characterized in that The method further comprises a packaging step to at least encapsulate the light-emitting layer.

Citation Information

Patent Citations

  • Preparation method of patterned quantum dot film light-emitting device

    CN116963566A

  • Method for preparing high-density full-color QLED device by using full ink-jet printing

    CN117835769A

  • Perovskite quantum dot dispersion liquid for ink-jet printing and photoetching patterning, preparation method, printing method, photoetching patterning method and application

    CN118530626A

  • POSS (Polyhedral Oligomeric Silsesquioxane)-based quantum dot photoresist, quantum dot film and application thereof

    CN118567181A

  • Solvent-free photocuring quantum dot ink and application thereof

    CN118580717A

Cited By

  • POSS (Polyhedral Oligomeric Silsesquioxane) connection-based quantum dot photoresist composite material and preparation method and application thereof

    CN121471903A

  • Quantum dot photoresist composite based on poss connection and preparation method and application thereof

    CN121471903B